2011
DOI: 10.1002/anie.201100961
|View full text |Cite
|
Sign up to set email alerts
|

Radical Derivatives of Insoluble La@C74: X‐ray Structures, Metal Positions, and Isomerization

Abstract: Insoluble fullerenes solubilized: Addition of dichlorophenyl radicals to insoluble La@C74 affords two series of regioisomers in which dichlorophenyl groups with different substitution patterns are singly bonded to one of two adjacent cage carbon atoms. X‐ray diffraction studies reveal that the internal metal atom is responsible for such addition patterns, while addition to different sites modifies the motion of the metal atom (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 30 publications
3
63
1
Order By: Relevance
“…Because there is an unpaired electron distributed on the cage of the pristine Y@C 66 , an odd number of addition groups are needed to form a closed‐shell configuration. This situation is similar to some cases of trivalent metallofullerenes, M III @C 2 n (M=Y or La; 2 n =60, 70, 74, or 82), reported previously . In addition to the mono‐trifluoromethylated derivative of Y@C 66 , polyalkylation adducts can also be generated in experiments.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Because there is an unpaired electron distributed on the cage of the pristine Y@C 66 , an odd number of addition groups are needed to form a closed‐shell configuration. This situation is similar to some cases of trivalent metallofullerenes, M III @C 2 n (M=Y or La; 2 n =60, 70, 74, or 82), reported previously . In addition to the mono‐trifluoromethylated derivative of Y@C 66 , polyalkylation adducts can also be generated in experiments.…”
Section: Resultssupporting
confidence: 86%
“…A carbon atom having a large pyramidalization angle prefers to form a fourth covalent bond through an addition reaction to relieve the steric strain. As compared with other reported metallofullerenes such as La@C 74 , most of the carbon atoms in the fused pentagon region for Y@ C 2 v (4348)‐C 66 , including C43, C42, C31, and C30, have a high spin density and/or a large pyramidalization angle (Table ). Furthermore, C4 also has a high spin density.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Encapsulation of metal atoms or metal clusters inside fullerene cages affords ac ollection of novel molecules, which are called endohedral metallofullerenes (EMFs). [1][2][3][4] Thec harge transfer from the internal unit to the fullerene cage gives rise to the important properties of EMFs.Based on the charge localized on the fullerene cage,two types of EMFs could be identified:o pen-shell EMFs with an unpaired electron residing on the cage or closed-shell EMFs containing only paired electrons.S ignificantly,o pen-shell EMFs have ahigh reactivity toward radical reactions because of their own radical character.F or instance,several insoluble mono-EMFs such as La@C 2n (2n = 72, 74, 80, 82) [5][6][7][8][9] were solubilized during a1 ,2,4-trichlorobenzene extraction process.T he discovery of these insoluble EMFs was achieved because these highly reactive,o pen-shell EMFs can be transformed into stable,c losed-shell derivatives through radical coupling reactions with dichlorophenyl radicals.A dditionally,t he reaction between La@C 82 and toluene [10] also revealed that the open-shell La@C 82 is able to convert into ac losed-shell derivative.S imilarly,a nu nexpected NO 2 radical addition occurred when anthranilic acid and isoamyl nitrite reacted with La@C 82. [11] TheC F 3 radical generated by thermolysis of CF 3 Io rA g(CF 3 CO 2 )c an be readily attached to EMFs.…”
Section: Dedicated To Professor Zhennan Gu On the Occasion Of His 80tmentioning
confidence: 99%
“…[1][2][3][4] Thec harge transfer from the internal unit to the fullerene cage gives rise to the important properties of EMFs.Based on the charge localized on the fullerene cage,two types of EMFs could be identified:o pen-shell EMFs with an unpaired electron residing on the cage or closed-shell EMFs containing only paired electrons.S ignificantly,o pen-shell EMFs have ahigh reactivity toward radical reactions because of their own radical character.F or instance,several insoluble mono-EMFs such as La@C 2n (2n = 72, 74, 80, 82) [5][6][7][8][9] were solubilized during a1 ,2,4-trichlorobenzene extraction process.T he discovery of these insoluble EMFs was achieved because these highly reactive,o pen-shell EMFs can be transformed into stable,c losed-shell derivatives through radical coupling reactions with dichlorophenyl radicals.A dditionally,t he reaction between La@C 82 and toluene [10] also revealed that the open-shell La@C 82 is able to convert into ac losed-shell derivative.S imilarly,a nu nexpected NO 2 radical addition occurred when anthranilic acid and isoamyl nitrite reacted with La@C 82. [1][2][3][4] Thec harge transfer from the internal unit to the fullerene cage gives rise to the important properties of EMFs.Based on the charge localized on the fullerene cage,two types of EMFs could be identified:o pen-shell EMFs with an unpaired electron residing on the cage or closed-shell EMFs containing only paired electrons.S ignificantly,o pen-shell EMFs have ahigh reactivity toward radical reactions because of their own radical character.F or instance,several insoluble mono-EMFs such as La@C 2n (2n = 72, 74, 80, 82) [5][6][7][8][9] were solubilized during a1 ,2,4-trichlorobenzene extraction process.T he discovery of these insoluble EMFs was achieved because these highly reactive,o pen-shell EMFs can be transformed into stable,c losed-shell derivatives through radical coupling reactions with dichlorophenyl radicals.A dditionally,t he reaction between La@C 82 and toluene [10] also revealed that the open-shell La@C 82 is able to convert into ac losed-shell derivative.S imilarly,a nu nexpected NO 2 radical addition occurred when anthranilic acid and isoamyl nitrite reacted with La@C 82.…”
mentioning
confidence: 99%